Managing career transitions your career as a work in progress - Hayes, Kit Harrington (Prentice Hall, 2000)
For courses in Career Development/Transition. This text addresses the unique needs of recareering students, mainly adults, providing them with a six-step model for the process of career transition. It addresses career-planning issues relevant to today's rapidly changing and highly competitive market.